Evaluation by different methodologies of collapse potential of some residual soils in Aburrá and San Nicolás Valleys (2015)
The process of precipitated variation of a soil volume when subjected to increase in stresses which withstand and/or the degree of saturation, it’s also known as collapse. Collapse Potential of soils can be determined from correlations derivative of the material properties index. That’s why in this work, it was evaluated using different methods the Collapse Potential of soils for ten specimens of tropical residual soils coming from five different points in Aburrá and San Nicolás Valleys, and the results were compared with the index collapse obtained using the duple-oedometer test. It was achieved to establish which of the procedures is closer to the traditional test results, and thereby obtain an approximation to the potential collapse using easy implementation methodologies with significant costs savings and rehearsal times, without loss of reliability evaluation.